2016
DOI: 10.1002/asmb.2179
|View full text |Cite
|
Sign up to set email alerts
|

Principal component models with stochastic mean‐reverting levels. Pricing and covariance surface improvements

Abstract: a In this work, we create a family of simple stochastic covariance models, which display stochastic mean-reverting levels of covariance as an additional level of stochastic behavior beyond well-known stochastic volatility and correlation. The one-dimensional version of our model is inspired by Heston model, while the multidimensional model generalizes the principal component stochastic volatility model. Their main contribution is that they capture stochastic mean-reversion levels on the volatility and on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The energy sector appears in the second position, since it also has volatile and unpredictable data (Dong et al, 2020). The main variables used were: option prices (European and American options, energy prices and simulated data); stock exchange indexes (S&P 500, CSI 300 and DJIA); personal income; and mean residence time (Balajewicz and Toivanen, 2017;Bi et al, 2016;Kyriakou et al, 2016;Li et al, 2016;Masoliver and Perelló, 2007;Richmond and Sabatelli, 2004). The application format of these variables were spot data (48%), variance swaps (28%) and series of returns (24%).…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The energy sector appears in the second position, since it also has volatile and unpredictable data (Dong et al, 2020). The main variables used were: option prices (European and American options, energy prices and simulated data); stock exchange indexes (S&P 500, CSI 300 and DJIA); personal income; and mean residence time (Balajewicz and Toivanen, 2017;Bi et al, 2016;Kyriakou et al, 2016;Li et al, 2016;Masoliver and Perelló, 2007;Richmond and Sabatelli, 2004). The application format of these variables were spot data (48%), variance swaps (28%) and series of returns (24%).…”
Section: Meta-analysismentioning
confidence: 99%
“…In Figure 8, "stochastic volatility" is the most quoted term, as the Heston model is a very successful closed-form model based on stochastic volatility (Zhu and Lian, 2012). Other trend topics are related to the justifications of the studies, since the Heston model is able to describe the dynamics of assets pricing and variance swaps (Balajewicz and Toivanen, 2017;Bi et al, 2016;Cao and Fang , 2017;Dong et al, 2020). In summary, the Heston model is a very well evaluated and widely used method in the financial area.…”
Section: Meta-analysismentioning
confidence: 99%
“…Bi et al. investigate derivatives pricing with stochastic mean‐reverting levels in the principal component of the stochastic variance–covariance matrix. Zhu and Lian derive the closed‐form pricing formula for the discretely sampled variance swap under the Heston stochastic volatility (SV) model using a partial differential equation (PDE) approach.…”
Section: Introductionmentioning
confidence: 99%
“…( 9) is an SVM where the speed of mean-reversion of v t is stochastic, but fully correlated with v t . In the literature, there have been already some attempts to consider an extension of the Heston model by assuming the mean-reversion level θ to be stochastic; see [32,16]. In particular, in [32] it is shown that such a model is able to replicate a term structure of VIX (CBOE volatility index) options.…”
mentioning
confidence: 99%